Cutaneous vasculitis in a child with community acquired pneumonia - M., Sakti Priya; Subbarao, Pinnaka; P., Ramachandran; J., Dinesh Kumar (International Journal of Contemporary Pediatrics, 2020)
Mycoplasma pneumoniae is an important etiological agent in community acquired pneumonia (CAP) in children aged 3 to 15 years. Mycoplasma pneumoniae may present with varied extra pulmonary manifestations. A 5 year old child presented with cough and fever and was initially managed as CAP due to Streptococcus pneumoniae. Child continued to have fever spikes and worsening distress and developed pleural effusion. Mycoplasma immunoglobulin M (IgM) was raised and child was treated with azithromycin. After 10 days of admission, the child developed fissuring of lips and discoloration of extremities. Direct Coombs test, cold agglutination test, antinuclear antibody (ANA) and anticardiolipin antibody were positive. Suspecting small vessel vasculitis, she was started on enoxaparin and aspirin and improved well. This case of CAP due to Mycoplasma pneumoniae is presented for the rare extrapulmonary manifestation of cutaneous vasculitis.